Upper Trunk Brachial Plexus Palsy Following Chiropractic Manipulation - John Cunningham; Wayne Hoskins; Wayne Hoskins; Scott Ferris (Frontiers in Neurology, 2016)
Introduction:Upper trunk brachial plexus palsy can result from high energy trauma and has never been reported following spinal manipulation.Background:The case is presented of a patient who developed an acute brachial plexus upper trunk palsy following spinal manipulative therapy. Discussion:Discussion is made on the incidence of complications following manipulation and recommendations to prospectively capture all serious complications.Concluding Remarks:Risks exist with spinal manipulative therapy. Neurological injury can occur. Risk assessment and re-examination should occur at every visit. Large rigorous prospective studies are required to identify the true incidence of serious complications resulting from manipulative therapy and the benefit:risk ratio.